The Meaning of Prayer in the Qur'an as a Response to Contemporary Moral and Spiritual Crises - Nurhidayah, Elva; Fitri Ariska; Agustiar (STKQ Al-Hikam Depok, 2025)
The moral and spiritual crisis has become an increasingly prominent phenomenon in contemporary society, marked by a weakening orientation towards divine values, rising materialism, and the degradation of individual and social ethics. This study aims to thematically analyze verses from the Qur'an about prayer and relate them to the reality of the contemporary moral and spiritual crisis in order to demonstrate their theoretical and practical relevance. This study uses a qualitative-descriptive approach through a literature review with primary data in the form of Qur'anic verses related to prayer, specifically QS. Al-Baqarah [2]: 43, QS. Thaha [20]: 14, and QS. Al-'Ankabut [29]: 45, as well as secondary data from tafsir literature and scientific articles. Data analysis was carried out using a thematic (maudhu'i) tafsir approach. The results of the study show that prayer in the perspective of the Qur'an has integrated theological, spiritual, moral, and social dimensions and functions as a means of forming divine consciousness and human ethics. This study concludes that prayer is a relevant Qur'anic response to the moral and spiritual crisis in the modern era.